Anne Frank remembered the story of the woman who helped to hide the Frank family - Gies, Miep 1909-2010.; Gold, Alison Leslie (New York Simon and Schuster, 1987)
Miep Gies, the woman who helped to hide the Otto Frank family during World War II, describes her own childhood and later association with the Franks and others she helped to hide from the Nazis.
Includes index.
Keywords: Gies, Miep -- 1909-2010.; Frank, Anne -- 1929-1945.; Righteous Gentiles in the Holocaust -- Netherlands -- Amsterdam -- Biography; Holocaust, Jewish (1939-1945) -- Netherlands -- Amsterdam; Amsterdam (Netherlands) -- Ethnic relations